2017
DOI: 10.1002/fsn3.570
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Boiling and roasting on lipid quality, proximate composition, and mineral content of walnut seeds (Tetracarpidium conophorum) produced and commercialized in Kumba, South‐West Region Cameroon

Abstract: The effect of boiling and roasting on the lipid quality, proximate composition, and mineral content of African walnut seeds (Tetracarpidium conophorum) was assessed. Results indicated that the quality of walnut oil significantly (p < .05) reduces with the treatments. Oils extracted from DBWN 60 min (Dried and boiled walnuts 60 min) and FBWN 60 min (Boiled fresh walnuts 60 min) were the most altered. The proximate composition and mineral content of walnut seeds was also significantly affected (p < .05) by the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
9
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 16 publications
8
9
2
Order By: Relevance
“…The value for phosphorus in this study was higher in boiled nuts than in fresh nuts contrary to the report of Djikeng et al (2017) who reported a decrease in phosphorus concentration (between 16.86 and 22.38 mg/100g) in all the cooked samples. The result obtained in this study was higher than 35 mg/100g previously reported by Nwaoguikpe et al (2012).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The value for phosphorus in this study was higher in boiled nuts than in fresh nuts contrary to the report of Djikeng et al (2017) who reported a decrease in phosphorus concentration (between 16.86 and 22.38 mg/100g) in all the cooked samples. The result obtained in this study was higher than 35 mg/100g previously reported by Nwaoguikpe et al (2012).…”
Section: Discussioncontrasting
confidence: 99%
“…Boiling boosted the amount of iron in walnut and this indicated that, boiling for 60 minutes as was done in this study was suitable for the release of iron in walnut seeds. This result agrees with the report of Djikeng et al (2017) that higher values of iron were obtained in boiled nuts than in the raw nuts (28.81 and 20.84 mg/100g, respectively). The amount of iron provided by walnut can help alleviate or prevent nutritional anemia associated with iron deficiency.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It is one of the most common processing methods used in Africa and this helps to improve the functional properties of food products [ 7 ]. The application of dry heat to food facilitate browning reaction thereby improving the nutritional property of leguminous seeds [ 8 ]. Although heat treatment has been reported to boost the antioxidant property of foods [ 9 , 10 ], it could cause significant changes to product quality when heated at high temperature.…”
Section: Introductionmentioning
confidence: 99%